2015
DOI: 10.2807/1560-7917.es.2015.20.46.30066
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care unit surveillance of influenza infection in France: the 2009/10 pandemic and the three subsequent seasons

Abstract: During the 2009/10 pandemic, a national surveillance system for severe influenza cases was set up in France. We present results from the system's first four years. All severe influenza cases admitted to intensive care units (ICU) were reported to the Institut de Veille Sanitaire using a standardised form: data on demographics, immunisation and virological status, risk factors, severity (e.g. acute respiratory distress syndrome (ARDS) onset, mechanical ventilation, extracorporeal life support) and outcome. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
24
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 21 publications
6
24
1
4
Order By: Relevance
“…A fatal outcome was predominantly associated with A/H1N1pdm09 infection and patients in the age group 30-64 years had the highest probability of a fatal outcome. Our data are consistent with findings from other countries showing that adults were at higher risk of death than younger patients when infected with A (H1N10pdm09 viruses [25][26][27][28]. The vast majority of fatal cases suffered with at least one chronic condition, with cardiovascular and neurological disorders being the leading comorbidities.…”
Section: Discussionsupporting
confidence: 91%
“…A fatal outcome was predominantly associated with A/H1N1pdm09 infection and patients in the age group 30-64 years had the highest probability of a fatal outcome. Our data are consistent with findings from other countries showing that adults were at higher risk of death than younger patients when infected with A (H1N10pdm09 viruses [25][26][27][28]. The vast majority of fatal cases suffered with at least one chronic condition, with cardiovascular and neurological disorders being the leading comorbidities.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, infection with virus influenza A (H3) was a protective factor, independently associated with admission to hospital without ICU. A French study reported similar findings for infection with A (H3N2) (17).…”
Section: Discussionsupporting
confidence: 59%
“…Our results suggest that influenza is associated with substantial morbidity in terms of primary care attendances due to ILI and hospitalizations T A B L E 1 Influenza by (sub)type, ILI and catchment population of the sentinel surveillance system by age in Romania in 2011/12-2015/16 influenza seasons 20 and in Greece, during the 2010/2011 (post-pandemic) season, the CFP was 39%. 21 This could be explained by more patients being recruited in critical condition, when they were more likely to die, while others, less severe, might not have been captured; however, this does not explain the large variability between seasons.…”
Section: Discussionmentioning
confidence: 94%